2017
DOI: 10.1016/j.metabol.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin 4 receptor is not required for estrogenic regulations on energy homeostasis and reproduction

Abstract: Background Brain estrogen receptor-α (ERα) is essential for estrogenic regulation of energy homeostasis and reproduction. We previously showed that ERα expressed by pro-opiomelanocortin (POMC) neurons mediates estrogen’s effects on food intake, body weight, negative regulation of hypothalamic–pituitary–gonadal axis (HPG axis) and fertility. Results and conclusions We report here that global deletion of a key downstream receptor for POMC peptide, the melanocortin 4 receptor (MC4R), did not affect normal negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
0
12
1
Order By: Relevance
“…For example, compared to male mice, female mice hypothalamus have more Pomc mRNA, POMC projections, and display higher neural activities [53,54]. Recent work by Xu et al, [55] found that loss of the MC4R did not influence estrogenic regulation on food intake, energy expenditure and bodyweight. This may explain the difference in body weight, food intake and energy expenditure between male and female C2CD5KO mice compared to their WT counterparts (Figure 2; Supplementary 1, 2).…”
Section: Resultsmentioning
confidence: 99%
“…For example, compared to male mice, female mice hypothalamus have more Pomc mRNA, POMC projections, and display higher neural activities [53,54]. Recent work by Xu et al, [55] found that loss of the MC4R did not influence estrogenic regulation on food intake, energy expenditure and bodyweight. This may explain the difference in body weight, food intake and energy expenditure between male and female C2CD5KO mice compared to their WT counterparts (Figure 2; Supplementary 1, 2).…”
Section: Resultsmentioning
confidence: 99%
“…For example, compared to male mice, female mice hypothalamus has more Pomc mRNA, POMC projections, and display higher neural activities [53,54]. Recent work by Xu et al [55] found that loss of the MC4R did not influence estrogenic regulation on food intake, energy expenditure and bodyweight. This may explain the difference in body weight, food intake and energy expenditure between male and female C2CD5KO mice compared to their WT counterparts ( Fig.…”
Section: Effects Of Mtii Are Impaired In Mice Lacking C2cd5mentioning
confidence: 99%
“…Disruption of MC4R in mice resulted in an obese phenotype, underscoring the potential role of MC4R in obesity [15,16]. Mutations in the MC4R are a relatively common cause of severe obesity [17][18][19][20]. Humans with MC4R mutations led to either gain [21] or loss of function [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Our data clearly identify estrogen as a potent signal for increasing Mc4r expression akin to the gain-offunction human MC4R variants that attenuate receptor internalization, which also protect against weight gain 33 . We predict that melanocortin insensitivity in E2-responsive VMHvl neurons partially accounts for the increased sedentary lifestyle associated with estrogen-depletion following menopause 34 , while acknowledging that the benefits of estrogen on healthy metabolism likely involve additional MC4R-independent processes 35 .…”
Section: Discussionmentioning
confidence: 89%
“…(RM 2-way ANOVA female interaction effect F(1,8)=27.48, P=0.0008, post hoc P<0.0001 and male interaction effect F(1,7)=36.27, P=0.0005, post hoc P<0.0001) d, Food consumption over a 5 hr period following CNO injection during the light (ZT4) or dark (ZT12) phase. e, VMHvl MC4R::hM3Dq females maintained on HFD with chronic chemogenetic stimulation (RM 2-way ANOVA interaction effect F(5,35) =4.837, P=0.0018, post hoc: P=0.0010, 0.0088, 0.0014, and 0.0073). Body weights of VMHvl MC4R::hM3Dq mice during the first 48 hrs of CNO exposure (unpaired 2-tailed t test t(8) =4.963, P=0.0011).…”
mentioning
confidence: 99%